INTERPRETING TOLERANCE FROM A LOCAL PERSPECTIVE: AGH. DAUD ISMAIL’S THOUGHTS ON INTERFAITH RELATIONS IN TAFSIR AL-MUNIR - Abdul Mutakabbir (Universitas Nurul Jadid, 2025)
The phenomena of religious intolerance and conflict continues to pose a serious challenge in multicultural societies both at the national and global levels. This situation underscores the importance of formulating a concept of religious tolerance that is not merely normative, but also contextual and rooted in local scholarly traditions. In this context, Nusantara exegesis plays a strategic role in articulating a moderate Islamic perspective that is relevant to social realities. This article aims to analyze the concept of interfaith tolerance in Tafsir Al-Munir by AGH. Daud Ismail as a representation of local Qur’anic interpretation in responding to contemporary global issues of tolerance. This study employs a qualitative approach using library research methods. The primary source of data is Tafsir Al-Munir written in Lontara script, while secondary sources include books, journal articles, and other relevant studies. Data were analyzed through content analysis of Qur’anic verses and exegetical discussions related to interreligious tolerance. The results of the study show that Daud formulates tolerance in two forms, namely passive tolerance and active tolerance. Passive tolerance is applied to matters of faith and worship that manifested in the prohibition of coercion in belief and rejection of ritual syncretism. Active tolerance, on the other hand, is applied within the socio-communal sphere and is reflected in principles of communication, cooperation, social justice, and rejection of hate speech. The study concludes that Daud Ismail’s thought makes an important contribution to the development of Nusantara Qur’anic interpretation and the broader discourse on religious moderation. Implicitly, the framework of active-passive tolerance offers a relevant reference for religious education and the promotion of social harmony grounded in local wisdom without obscuring the fundamental religious principles.